Implementasi Failure Mode Effect Analysis Dalam Pengendalian Kualitas Produk: Studi Literatur - Daffa Satrio Utomo; Triana Ambarwati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to identify the application of Failure Effect Analysis (FMEA) mode and analyze the integration of Failure Effect Analysis (FMEA) with other methods. The research method used in this research is qualitative with a literature review approach. The research stages begin with collecting articles, reducing articles, displaying articles, discussion, and conclusions. The research data sources are national journal articles in the last 7 years (2018 - 2024). The results showed that Failure Effect Analysis (FMEA) can be applied in various industries, not only limited to one or two industries. Failure Effect Analysis (FMEA) can be integrated with other types of methods that are in accordance with the research objectives. In the application of Failure Effect Analysis (FMEA) combined with other types of methods, there are no definite rules regarding the order in which the methods are used, this can be adjusted to the research objectives that have been formulated.